Effects of estradiol, progesterone and kisspeptin-1 concentrations at the time of insemination on conception rates in cattle - Kaya, S; Kaçar, C; Arı, UC; Merhan, O; Demir, MC; Bekyürek, T; Gürbulak, K (Journal of the Hellenic Veterinary Medical Society, 2023)
The present study aimed to investigate the effects of kisspeptin (Kiss-1), estradiol (E2), and progesterone (P4) levels at the time of artificial insemination (AI) on conception rates and also whether or not there is a relationship between Kiss-1 and E2 levels in cattle. Cows (n=100) raised on a semi-closed farm system and having corpus luteum were administered 25mg of prostaglandin F2a (Dinolytic®, Zoetis, Spain) and were evaluated following injection for signs of estrus. Just prior to AI, pre-ovulatory follicle diameters were assessed by ultrasonography (USG) and recorded. Then blood samples were collected. Blood serum samples were separated and stored until analyzed. Pregnancies were determined with rectal USG on day 30±2 following AI. The mean follicular diameters at the time of AI were similar in pregnant (17.9±0.01 mm) and non-pregnant (17.9±0.01 mm) cows. E2, P4, and Kiss-1 levels at the time of AI were determined from serum samples using the ELISA method. The Kiss-1 level at the time of AI in pregnant cows (80.58±4.4 pg/mL) was statistically higher than that in non-pregnant cows (66.68±2.48 pg/mL) (P=0.003). There were no statistically significant differences in E2 and P4 levels between pregnant and non-pregnant cows. Moreover, while a significant correlation was found between serum kiss-1 level and follicle diameter, no significant correlation was found between serum estrogen and progesterone levels. In conclusion, Kiss-1 levels at the time of AI may be used to predict the possibility of successful pregnancy in cattle, allowing different approaches to be developed to increase pregnancy rates in animals with low Kiss-1 levels at the time of AI.